2020
DOI: 10.1111/exd.14171
|View full text |Cite
|
Sign up to set email alerts
|

Generalized pustular psoriasis—Dawn of a new era in targeted immunotherapy

Abstract: Generalized pustular psoriasis (GPP) is a chronic, non-communicable inflammatory skin disease which can involve multiple organs and potentially lead to a fatal outcome. GPP is characterized by acute, recurrent flares of sterile pustular lesions on erythematous skin with signs of systemic inflammation also affecting extracutaneous organs. It can be associated with a pre-existing plaque psoriasis or develop independently. Due to its low prevalence, it is defined as an orphan disease. 1-3 In our review article of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
0
25
0
1
Order By: Relevance
“…Nevertheless, the levels of its expression in the lesional skin of GPP patients are significantly lower than in patients with plaque psoriasis [23]. Due to the IL-36 pathway intertwining with the TNF-α/IL-23/IL-17/IL-22 axis, a positive inflammatory feedback loop is created, as explained above [110,111]. IL-17A promotes the chemotaxis and accumulation of inflammatory cells, such as neutrophils, at the sites of inflammation.…”
Section: Il-17/il-36 Axis As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 99%
“…Nevertheless, the levels of its expression in the lesional skin of GPP patients are significantly lower than in patients with plaque psoriasis [23]. Due to the IL-36 pathway intertwining with the TNF-α/IL-23/IL-17/IL-22 axis, a positive inflammatory feedback loop is created, as explained above [110,111]. IL-17A promotes the chemotaxis and accumulation of inflammatory cells, such as neutrophils, at the sites of inflammation.…”
Section: Il-17/il-36 Axis As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 99%
“…Association between IL‐15 single nucleotide polymorphisms (SNPs) and PSO has been reported, 22 and an ex vivo co‐culture study found that IL15 synergizes with IL23 to activate cutaneous lymphocyte‐associated antigen (CLA)+ T cells to produce high levels of IL17A/F 21 . Compared to PSO, generalized pustular psoriasis expresses higher levels of IL1 and IL36 in the skin, 23 in addition to IL17 and IL23, leading to excessive and persistent skin inflammation that can manifest systemically 23 …”
Section: Immunopathogenesismentioning
confidence: 99%
“…In contrast to psoriasis, 1‐25 atopic dermatitis 26‐47 and pruritus 21,35,48‐70 whose therapeutic landscapes have dramatically changed over the last few years due to many advances in skin research, scleroderma remains a challenge in many aspects.…”
mentioning
confidence: 99%